Simultaneous representations of explanatory characteristics of mergers - R. C. Van Den Honert; G. D.I. Barr (South African Journal of Business Management, 1988)
In this paper we consider the effect of various explanatory characteristics on target and acquiring firm shareholder's wealth using a specialized graphical technique. Whereas previous analyses have considered each of the characteristics in isolation we analyse all the characteristics simultaneously by using the covariance biplot. By analysing the resulting single diagram for acquiring firms and target firms we are able to present information about the relative variability or riskiness of each level of the five characteristics, as well as about their co-movement.
Keywords: 650